The prevalence and effective factors of crash helmet usage among motorcyclists in Iran - Heydari, Seyed Taghi (J Inj Violence Res, 2016)
BACKGROUND: Crash helmet plays an important role in protecting the deriver's head during crashes and reduces the rate of severe injuries and fatalities. Although it has been proved that wearing the crash helmet can save the deriver’s life by around 42%; previous studies showed that the rate of wearing crash helmet has not been acceptable in Iran. Due to the huge number of motorcyclists on the roads in Iran, the use of crash helmet is an important area of research. The aim of this study was to assess the factors that could possibly relate to or affect the use of crash helmet by the motorcyclists. METHODS: This is an observational study on 414 motorcyclists in Shiraz, Southern Iran. All participants completed a questioner containing demographic features, crash helmet use, motorcycle license, and the reasons for using motorcycles. RESULTS: All the participants were males and aged from16 to 64 years with mean age 27±9.28. The results of logistic regression model revealed that only the drivers who had motorcycle license (OR=2.73, C.I: 1.40-7.24), employed the motorcycle for reasons other than pleasure (OR=3.18, C.I: 1.42-7.37) and been driving for 10 or more years (OR=1.92 95% C.I: 1.12-3.30) had greater rate of wearing crash helmet. Interestingly, educational levels, age, and other demographical variables had no relationship with crash helmet usage. CONCLUSIONS: It is believed that in order to increase the rate of crash helmet use, it is necessary to enact obligatory requirement for driving license by motorcyclists and increase the legal age for motorcycle driving.